PENERAPAN FUNGSI JAKSA SEBAGAI EKSEKUTOR TERHADAP HUKUMAN KEBIRI DALAM TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP ANAK DI INDONESIA - NR. Merry Meriawati; Efa Laela Fakhriah; Hernawati RAS (Scientia Regendi, 2021)
The number of crimes of sexual violence against children in Indonesia is very high, the government is very concerned about this, thus issuing a Government Regulation in Lieu of Law (Perpu) on Child Protection, which regulates the punishment for castration for these perpetrators, this Perpu was then promulgated by law. Act 17/2016, and the technical implementation of this castration action will be regulated in a government regulation that will be made next, however until June 2020, the Government Regulation which will regulate how the technical implementation of castration has not been published, so this will cause several problems. law, How is the execution of castration in Indonesia, How is the effect of castration punishment in terms of the objective aspect of the punishment against perpetrators of crimes of sexual violence against children in Indonesia.The approach method used in this research is the normative juridical approach, which is a study that emphasizes statutory regulations to study problems by finding legal regulations that aim to discover legal principles and theories which are then established in practice. The research specification is descriptive analytical, which describes and analyzes problems based on relevant laws and regulations, so that legal facts can be obtained in society. The data collected were analyzed using qualitative juridical analysis methods, namely the data obtained were arranged systematically, then described in narrative form without using statistical formulas or figures.In its implementation, the castration sentence stipulated in the Child Protection Law has encountered difficulties, because the technical rules for its implementation which will be made in the form of government regulations until June 2020 have not been published, the prosecutor as executor of the sentence on the court's decision should continue to carry out the judge's decision immediately castration punishment as regulated by law needs to be implemented immediately in accordance with the statutory order. The current trend for sexual violence against children has not decreased, however, it cannot always be said that castration is ineffective, because the implementation of the sentence has not been carried out until June 2020 ,. In addition to the chemical castration punishment, which has a temporal effect, it should also be imitated as in the United States, that the punishment for perpetrators of sexual violence against children is cumulative, this is done because the effects of this crime of sexual violence are very destructive, so that the sentence imposed can reach limit of 200 years imprisonment, so the possibility of the perpetrator committing the crime again is almost impossible, and if there is an error in the verdict, it will be easy to carry out rehabilitation. Keywords: punishment for castration, sexual harassment, sexual violence